Econometric Analysis of Renewable Energy Consumption and Economic Growth: The Case of Kazakhstan and Kyrgyzstan - Sarkhanov, Teymur; Huseynli, Nigar (International Journal of Energy Economics and Policy, 2022)
Finding renewable resources against depleted resources has become very important in almost every field. Especially in the energy sector, the availability of renewable energy sources is of great importance. The aim of this study is to measure the effect of the renewable energy sector of Kazakhstan and Kyrgyzstan, which are selected Turkish states, on the growth of the economy. The data included in the analysis cover the period from 1996 to 2018. The variables included in the analysis as economic growth and renewable energy consumption were subjected to a series of assumption tests. As a final step, a conclusion was reached by applying regression analysis. It has been determined that there is a positive relationship between the economic growth in both countries and the renewable energy consumed in this country.